2015
DOI: 10.12965/jer.150242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of regular swimming exercise on the physical composition, strength, and blood lipid of middle-aged women

Abstract: The purpose of this study is to define the effects of regular swimming exercise on the physical composition, physical strength, and blood lipids of middle-aged women. The subjects of this study are a total of 24 middle-aged women in the swimming group and the control group, with 12 women for each group. The swimming group performed swimming exercise for 60 min every time for 3 times a week, for a total of 12 weeks. For data processing, SPSS 21.0 statistics program was used to calculate the mean and standard de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Moreover, blood flow and bone density during muscle activity are affected by FMM and are directly related to the ability to exercise (Lee & Oh, 2015). This study showed that there was no statistically significant difference in FMM and the absence of a significant reduction in this parameter may be due to the shorter duration of the WATERinMOTION program than other studies.…”
Section: Discussionmentioning
confidence: 46%
“…Moreover, blood flow and bone density during muscle activity are affected by FMM and are directly related to the ability to exercise (Lee & Oh, 2015). This study showed that there was no statistically significant difference in FMM and the absence of a significant reduction in this parameter may be due to the shorter duration of the WATERinMOTION program than other studies.…”
Section: Discussionmentioning
confidence: 46%
“…This may be due to the short-run implementation of WiM compared to other studies. Bone density and blood flow during muscular activity depend on FFM and are directly related to exercise (36). WiM provides this work by the built-in resistance from the viscosity of the water that makes the push through in any movement made (32).…”
Section: Discussionmentioning
confidence: 99%
“…Swimming is a very good physical exercise and regular swimming for a specific period helps in the overall up-gradation of physiological and physicochemical systems of our body 30 . In contrary, excessive swimming is generally considered as severe or exhaustive type of physical exercise which faces stress especially for oxygen supply, blood supply, and energy supply in a greater quantity to the active tissues.…”
Section: Discussionmentioning
confidence: 99%